The Impact of Sustainable Development and Social Responsibility on Quality Education - CHUMACEIRO HERNANDEZ, Ana Cecilia; HERNÁNDEZ GARCÍA DE VELA, Judith Josefina; VELAZCO HERNÁNDEZ, Jovana Cristina; LAGUSEV, Yuriy Mikhailovich; ROGOZHINA, Anna Pavlovna (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).05, 2022)
In recent years the educational system has opted to implement sustainable strategies that allow access, coverage, relevance, and quality of education. The University does not escape these realities combined and the need to generate a real impact on all its stakeholders. Thus, the challenge of training competent individuals to face the future is increasingly relevant. This research aims to reflect theoretically on the impact that Sustainable Development and Social Responsibility effectively have on quality university education. For which relevant theoretical elements have developed that support in the first instance the origins of sustainable development and social responsibility and the fundamental elements of each one of them and, in the second instance, it explains how these binomial favors quality, sustainable and relevant education. The method is served from the qualitative paradigm, documentary observation, and content analysis. Among the findings, it is found that education influences people and nations, which is why Universities must take on the challenge of responsible teaching. It is concluded that today higher education institutions are called to the teaching of excellence. In particular, training future specialists in the tourism and hospitality industry requires the approach when it is not enough to carry out substantive functions of the University: teaching, research, extension, and social projection, but they must be articulated with each other, to contextualize the student of the problems of the environment, sustainable development of the territory and how they can be solved.